BECOME A RELIABLE TRADER : Playing The Role Of Price As A Psychological Influence On Consumers - Pratiwi Pratiwi; Salsabillah Salsabillah (Jurnal PKM Manajemen Bisnis, 2021)
In simple terms, the principle of trading is to work for yourself. While the basic principle of doing business is to involve many parties in trading to achieve a bigger goal. Theoretically, being an entrepreneur is very difficult, but that doesn't mean it's impossible. Due to the fact, many business actors appear throughout the year. Therefore, it takes effort to learn to be an entrepreneur or businessman. For this reason, this service activity was carried out. The purpose of community service activities is to share knowledge, so that people can increase their capacity as entrepreneurs by optimizing their talents. The method of this activity is the presentation of material packaged in the form of learning. The end of this activity is to motivate the participants to dare to do business, starting with the most possible and minimal risk, for example becoming an agent, reseller, dropshipper, and so on. In addition, the participants were also given training on using the Market place, a place to sell digitally without capital. At the same time, teach how to become an agent or reseller at big stores. So that the participants get direct experience of entrepreneurship.